(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2002)
The intensity of lipid peroxidation in tissues of high vertebrates with chemiluminescence and spectrophotometer definition of the MDA-concentration (malonic dialdehid) was examined. The received facts demonstrate, that level of free-radical oxidation processes in the row fishes-amphibians-reptiles-mammalians decrease, and, probably, it is connected not only with increasing of nourishing degree of fat acids in lipids of tissues of organisms in this evolutionary row, but also with amplification of role of antioxidant system, controlling the intensity of these processes.